Mitogenomic architecture and phylogenetic placement of Ctenophthalmus yunnanus and Frontopsylla diqingensis: insights from comparative genomics - Tang, Shaobo; Chen, Lei; Wu, Jun; Chen, Bin; Liu, Shuang; Duan, Mingna; Jiang, Dandan; Gu, Wei; Zhang, Quanfu; Yang, Xing (Frontiers in Veterinary Science, 2025)
Fleas are among the most common hematophagous ectoparasites of mammals. In addition to causing allergic dermatitis and anemia, they can transmit various pathogens. Currently, molecular data on fleas remain relatively scarce. This study sequenced the complete mitochondrial genomes of Ctenophthalmus yunnanus (first mitogenome reported) and Frontopsylla diqingensis from Yunnan, China, using Illumina sequencing. Comparative analyses with existing flea mitogenomes available in NCBI included nucleotide diversity and selective pressure assessments. Phylogenetic trees were reconstructed based on the PCG123 and PCG12 datasets using the Maximum Likelihood (ML) and Bayesian Inference (BI) methods, respectively. The mitogenomes of C. yunnanus (15,801 bp) and F. diqingensis (15,878 bp) were circular double-stranded molecules. Both genomes comprised 37 genes. Analysis of the comparative genomic data revealed that most fleas examined possessed mitochondrial genomes approximately 16,000 bp in length, with an average AT content nearing 78%. Additionally, most species exhibited negative AT and GC skews. Among the 13 PCGs, the codons UUA, UUU, and AUU were used most frequently. Analysis of nucleotide diversity and selection pressure indicated that the cox1 gene exhibited the lowest values for both Pi and Ka/Ks. Phylogenetic analysis demonstrated that the families Ctenophthalmidae and Leptopsyllidae were paraphyletic. Divergence time estimation indicated that the most recent common ancestor of crown-group fleas diverged during the Cretaceous period, while the majority of extant lineages within Siphonaptera underwent diversification following the K-Pg boundary. This study provides valuable mitochondrial genomic data for fleas, which lays a foundation for future genetic and phylogenetic studies and advances our understanding of siphonapteran evolution.